The effect of diuresis on extravascular lung water and pulmonary function in acute decompensated heart failure. (18th January 2018) - Chase, Steven C.; Fermoyle, Caitlin C.; Wheatley, Courtney M.; Schaefer, Jacob J.; Olson, Lyle J.; Johnson, Bruce D.
Abstract: Aims: The effect of extravascular lung water (EVLW) and relationship to functional status as a result of acute decompensated heart failure (ADHF) are not well understood. We sought to quantify changes in clinical variables, EVLW, airway anatomy, spirometry, and diffusing capacity for carbon monoxide before and after treatment for ADHF. Methods and results: Fifteen patients were recruited within 24 h of hospital admission. Spirometry, diffusing capacity for carbon monoxide, and surrogates of EVLW by computed tomography were measured and were then repeated within 24 h of discharge. From the computed tomography (CT) scan, surrogates of EVLW were calculated from the distribution of CT attenuation of the lung tissue. Airways were segmented using theVIDA Apollo software. Patients were hospitalized for 4.6 ± 2.1 days, had 10 ± 4.8 L of fluid removed (7.0 ± 4.2 L between study visits), and lost 7.1 ± 4.9 kg. Patients had significant clearance of fluid from the lungs (per cent change: mean, 4.2 ± 6.1%; skew, 17.5 ± 27.0%; kurtosis, 37.6 ± 56.7%; full‐width half‐maximum, 10.2 ± 13.5%). Static lung volumes and maximal flows improved significantly (per cent change: forced vital capacity, 14.5 ± 13.6%; forced expiratory volume in 1 s, 15.9 ± 14.0%; forced expiratory flow at 25–75% of forced vital capacity, 27.2 ± 42.9%). The ratio of membrane conductance to capillary blood volume improved significantly (per cent change: alveolar–capillary membrane conductance/capillary blood volume, 23.4 ± 22.8%). Weight loss during hospitalization was significantly correlated with improved spirometry and diffusing capacity. Conclusions: Extravascular lung water contributes to the pulmonary congestive syndrome in ADHF patients, and its clearance is an important component of the improvement in pulmonary function as a result of inpatient treatment.